The Effect of Profitability, Audit Opinion, Audit Committee and Company Size on Audit Delay (Study of Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange in 2021-2023) - Rahmadani, Novi; Arum, Enggar Diah Puspa; Friyani, Rita (International Journal of Business and Applied Economics, 2024)
This study is useful for finfing the impact of profitability, audit opinion, the audit committee, and company size on audit delay. The population of this study, which takes a quantitative approach, consists of property and real estate companies that are listed on the IDX for the years 2021–2023. After a three-year research period, a sample of 32 (thirty-two) emitens out of a total of 96 (ninety-six) were selected utilizing the purposive sampling technique. Panel data regression, a hybrid of cross section and time series, is used in this research. The regression model used is the Fixed Effect Model (FEM) using E-Views 12 software. This research findings that audit opinion, audit committee and companay size influences audit delay but profitability has no effect on audit delay. For profitability, audit opinion, audit committee and company size simultaneously affect audit delay.